ws0010: Snapshot van de website www.abvvmetaal.be van ABVV-Metaal, genomen op 26/11/2018 - ABVV-Metaal
"Collection: ABVV-Metaal; Geharvest met HTTrack3.49-2 Level of description: File; Series: 703.W.1: www.abvvmetaal.be"